Poetry of Þórarinn Eldjárn - Olga Markelova (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
This publication presents Russian translations of poems by Þórarinn Eldjárn, one of the most prominent fi gures in the modern Icelandic poetry. Þórarinn is one of the very few modern Icelandic poets who regularly use fast poetic form, especially certain complicated forms of the older Icelandic poetical tradition. By the time when Þórarin’s fi rst book was published (1974), verse libre had become the dominating form in Icelandic poetry; therefore, the return to the fi xed forms (both Icelandic and continental) could be regarded as a manifestation of a radical aesthetical standpoint. As for the content of the poems, they sometimes address Icelandic cultural and literary legacy of the past, but this is not always supported by the traditional form.However, Þórarinn does not express romantic feelings for this legacy, but relates it to present-day realities and contemporary vocabulary, which can produce both comical and dramatical effect on the reader. In his poems for children, Þórarinn also makes active use of old forms.